Kewargaanegaraan Warga Negara Indonesia Eks Islamic State of Iraq and Syria - Risvonda Souhaly; Salmon Eliazer Marthen Nirahua; Vica Jillyan Edsti Saija (Faculty of Law Pattimura University, 2021)
Introduction: The presence of the Islamic State of Iraq and Syria influenced the Indonesian people who then left Indonesia to join the Islamic State of Iraq and Syria, then the fall of the Islamic State of Iraq and Syria create problems, including the fate of the Indonesians.Purposes of the Research: Based on this background, author aim to analize whether Indonesian citizens who support the Islamic State of Iraq and Syria could lose Indonesian citizenship.Methods of the Research: Method used is the normative juridical research method with statue approach and conceptual approach.Results of the Research: Based on the author’s research, Indonesian citizenship is regulated in Law Number 12 of 2006 concerning Citizenship and is further regulated in Government Regulation Number 2 of 2007 concerning Procedures for Acquiring, Losing, Cancellation, and Regain Citizenship of the Republic of Indonesia, which in Article 23 letters a to i of Law Number 12 of 2006 and article 31 paragraph (1) letters a to h of Government Regulation Number 2 of 2007 regulates the loss of Indonesian citizenship. Based on article 23 letter i of Law Number 12 of 2006, and article 31 paragraph (1) letter h of Government Regulation Number 2 of 2007, according to the author, Indonesian citizens who support the Islamic State of Iraq and Syria could lose their citizenship